Aceh Party Seen By Millennials In Bireuen Regency - ., Alfian; ., Taufik; ., Mulyadi; ., Zulhilmi (Journal of Ecohumanism, 2024)
The Aceh Party in Bireuen District, Aceh Province, has been successful in multiple elections, winning the mayoral election and occupying the majority seat for two terms. The party has played an active role in fostering democratic life and maintaining peace in the region, as well as influencing policy and promoting the development agenda. Despite a decline in the number of legislative seats in each election, the Aceh Party has managed to maintain its presence as a winner by acquiring parliamentary seats. However, it is important to note that the decline in legislative seats is not the sole factor that weakens the party’s existence. There are various factors that contribute to the declining electability of the Aceh Party, and further analysis is required to understand the overall impact on the party’s strength. This research aims to understand the views of the millennial generation on the Aceh Party, a local political party. Using a qualitative approach, the study explores how millennials perceive the party’s existence in the present day. It is important to explore the knowledge and insights of millennials, as it provides an understanding of their role in shaping the nation and state. The research hopes to promote millennial awareness and involvement in building national identity and democratic wisdom in Bireuen Regency. The study will employ a qualitative and descriptive method, using techniques such as interviews and documentation to collect and analyze data. This data is crucial in examining the perspectives of the millennial generation on the Aceh Party in Bireuen Regency, Aceh Province, ensuring accurate and reliable findings. The study conducted on the perception of the millennial generation in Bireuen Regency towards the Aceh Party reveals contrasting views. While the party’s existence is seen through a historical struggle lens and tends to be sectoral egoistic, the millennials view it more objectively, resulting in a decline in its political electability. The Aceh Party fails to engage and empower the millennials in promoting the party, thereby hindering its effectiveness. This disconnect is primarily due to the rapid growth of digital media and the information it disseminates. Consequently, the Aceh Party struggles to stay relevant in the current political landscape. As the millennial generation plays a significant role in Bireuen Regency, it is crucial to approach them in an adaptive manner, avoiding sectoral egos and exclusivity, and aligning with their evolving needs and preferences.